Analisis Tingkat Kepuasan Siswa terhadap Program Makan Bergizi Gratis di SMA Negeri 1 Manokwari dengan Pendekatan Mining - Titin Restiani Mendrofa; Hendry Hendry (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
The Free Nutritious Meal Program (MBG) aims to improve students' nutritional status and learning quality; therefore, a data-driven evaluation is required to assess its implementation effectiveness. This study seeks to analyze the influence of program implementation on student satisfaction and to identify the resulting satisfaction segments. The research employed a descriptive quantitative approach involving 499 respondents. Data were collected through a Likert-scale questionnaire covering variables of program implementation and student satisfaction. The analysis utilized MANOVA, K-Means Clustering, and one-way ANOVA. The MANOVA results indicated that all implementation variables significantly affected student satisfaction (Sig < 0.001), with compliance to nutritional standards emerging as the most dominant factor (Wilks' Lambda = 0.805; F = 23.634). The K-Means analysis produced three satisfaction clusters: high (314 students), moderate (172 students), and low (13 students). The ANOVA test confirmed significant differences among clusters (Sig < 0.001), with the availability of healthy food (F = 145.428) as the main distinguishing factor. The findings of this study indicate that food variety and the availability of healthy meals are the main factors distinguishing students' satisfaction levels; therefore, the MBG program should focus on improving these two aspects to enhance overall student satisfaction.